Research on international service marketing a state of the art - Pauwels, Pieter; Ruyter, Ko de (Elsevier JAI, 2005)
A truly international perspective emerges on the nature of service marketing across borders, as well as the internationalization strategies of service providers. This volume explores the research in international service marketing through the eyes of scholars from eight different countries on three continents.
State of the art report.
Keywords: Service industries -- Marketing.; Export marketing.; elektronické knihy; electronic books